2006
DOI: 10.1271/bbb.60015
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Soyprotein Interaction as Determined by Thermal Unfolding Experiments

Abstract: Chitosan interaction with soybean beta-conglycinin beta(3) was investigated by thermal unfolding experiments using CD spectroscopy. The negative ellipticity of the protein was enhanced with rising solution temperature. The transition temperature of thermal unfolding of the protein (T(m)) was 63.4 degrees C at pH 3.0 (0.15 M KCl). When chitosan was added to the protein solution, the T(m) value was elevated by 7.7 degrees C, whereas the T(m) elevation upon addition of chitosan hexamer (GlcN)(6) was 2.2 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…The results clearly indicated the protein channel was more resistant to thermal denaturation when bound to its sugar substrates, the degree of heat tolerance being greater with increasing binding affinity. Such observations have been reported in previous studies: for example, it was shown by Fukamizo's group that chitosan hexamer helped to stabilize the structure of the glucosamine-recognizing β3 conglycinin from soybean [37].…”
Section: Discussionsupporting
confidence: 83%
“…The results clearly indicated the protein channel was more resistant to thermal denaturation when bound to its sugar substrates, the degree of heat tolerance being greater with increasing binding affinity. Such observations have been reported in previous studies: for example, it was shown by Fukamizo's group that chitosan hexamer helped to stabilize the structure of the glucosamine-recognizing β3 conglycinin from soybean [37].…”
Section: Discussionsupporting
confidence: 83%
“…The results clearly indicated the protein channel 303 was more resistant to thermal denaturation when bound to its sugar substrates, the degree of heat tolerance 304 being greater with increasing binding affinity. Such observations have been reported in previous studies: 305 for example, it was shown by Fukamizo's group that chitosan hexamer helped to stabilize the structure of 306 the glucosamine-recognizing β3 conglycinin from soybean [37].…”
supporting
confidence: 71%
“…The increase in the thermal unfolding temperature of the enzyme in the presence of chitosan was attributed to the stabilization of protein through electrostatic interaction with chitosan. 12 At pH > pI, where protein and chitosan have opposite charges, complex formation of faba bean legumin 13 with chitosan gave a small positive enthalpy change in contrast to the strongly exothermic interaction of chitosan with -lactoglobulin. 14 However, these variable observations do not preclude predominantly electrostatic interaction: Schaaf and co-workers 15 showed that complexation of oppositely charge polyelectrolytes can be either exothermic or endothermic.…”
Section: Introductionmentioning
confidence: 99%